Immunohistochemistry The Ageless Biotechnology - Streckfus, Charles F. (IntechOpen, 2020)
Immunohistochemistry - The Ageless Biotechnology is a book that is ideal for undergraduate and graduate biomedical researchers, and medical and dental health professionals. It is a detailed text, which emphasizes the laboratory and clinical implications of immunohistochemistry. The text covers the advances of immunohistochemistry from its humble origins in the 1930s up to the new decade of 2020. The book also offers a review of the immunohistochemistry detection systems with emphasis on their principles, history, and their advantages. It also stipulates the limitations and delineates the factors that need to be considered for choosing an appropriate detection system for IHC applications. The book describes current laboratory techniques and new applications for the technology. As the reader will observe, the book provides new and useful information concerning the rapidly advancing field of immunohistochemistry.